Funding Financial Inclusion: Institutional Logics and the Contextual Contingency of Funding for Microfinance Organizations - Cobb, J. Adam; Wry, Tyler; Zhao, Eric Yanfei (Academy of Management Journal, 2016)
Microfinance is a promising tool for addressing the grand challenge of global poverty. Yet, while many studies have examined how microfinance loans affect poor borrowers, we know little about how microfinance organizations (MFOs) themselves finance their lending activities. This is a significant oversight because most MFOs do not self-fund their lending, but, rather, rely on loans from external funders. To better understand microfinance funding, we apply and extend the institutional logics perspective to analyze the lending practices of commercial and public funders, who together provide most of the capital for global microfinance. We argue that these funders adhere to financial and development logics, respectively, and that this leads them to invest in different types of MFOs. Yet, in the face of uncertainty, we suggest that the practices motivated by these logics will start to converge in ways that are problematic for a nation’s microfinance sector. Using a proprietary database of all traceable loans to MFOs from 2004 to 2012, we find strong support for our hypotheses. In particular, our findings show that the relationship between institutional logics and organizational practices is contextually contingent, and this insight contributes important understanding about the efficacy of microfinance as a poverty-reduction tool.